An update on oculocerebrocutaneous (Delleman‐Oorthuys) syndrome. Issue 4 (22nd December 2018) - Moog, Ute; Dobyns, William B.
Abstract: Oculocerebrocutaneous syndrome (OCCS) is a rare disorder characterized primarily by congenital skin, eye, and brain anomalies. The most distinctive findings are hypoplastic or aplastic skin defects; pedunculated, typically hamartomatous, or nodular skin appendages; cystic microphthalmia; and a combination of forebrain anomalies and a specific mid‐hindbrain malformation. Based on a review of 40 patients with OCCS, existing clinical criteria have been revised. Because of the asymmetric and patchy distribution of features, lack of recurrence in families, male preponderance and completely skewed X‐inactivation in one female, OCCS is hypothesized to result from postzygotic mosaic variants in an X‐linked gene. Whole exome and genome sequencing on blood DNA in two patients failed to identify pathogenic variants so far. In view of the overlapping features, in particular of the brain, of OCCS and Aicardi syndrome, both may be pathogenetically related or even result from different variants in the same gene. For the elucidation of the cause of OCCS, exome or genome sequencing on multiple lesional tissues is the primary goal.